2016
DOI: 10.1016/j.adaj.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported temporomandibular joint disorder symptoms, oral health, and quality of life of children in kindergarten through grade 5

Abstract: Background The objectives were to determine the percentage of children in Kindergarten through Grade 5 who reported TMD symptoms, to assess whether gender, race, and socioeconomic background mattered, and to explore the relationships between TMD and children’s oral health and oral health-related quality of life (OHRQoL). Methods Face-to-face interviews were conducted with 8,302 children in Kindergarten through Grade 5 (51% female/49% male; 53% African American/42% European American). Oral health screenings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 33 publications
5
18
1
Order By: Relevance
“…The pooled rates of TMDs and pain showed significant differences between females and males, which was in accordance with some studies (Inglehart et al, 2016;Tecco et al, 2011), while opposite to another (Hirsch, Hoffmann, & Türp, 2012). Females were found to be more vulnerable than males in this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The pooled rates of TMDs and pain showed significant differences between females and males, which was in accordance with some studies (Inglehart et al, 2016;Tecco et al, 2011), while opposite to another (Hirsch, Hoffmann, & Türp, 2012). Females were found to be more vulnerable than males in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Slede argued that Asian Americans had a lower prevalence of TMDs, while African Americans had a higher incidence of TMDs when compared to the white (Slade et al, ). Meanwhile, Inglehart observed a significantly higher percentage of African American children who suffered from TMDs than white children, which is consistent with previous studies (Inglehart, Patel, Widmalm, & Briskie, ). However, more evidence is required to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The majority of adolescents in our study were classified as Class C (60.7%) and for this reason, showed no statistical association between the variables (p=0.507). However, in the literature there were results in agreement with our study [7] and others in disagreement [14, 22], probably because of the difference in the diagnostic criteria and age groups.…”
Section: Discussionsupporting
confidence: 91%
“…Such individuals are also less exposed to risk factors such as precarious housing, nutrient-poor foods [21]. A research demonstrated that the poverty is an important condition to exhibit myofascial pain and joint problems [19] and a recent study [22] showed a significant association between symptoms of temporomandibular joint disorder (TMJD) with poorer oral health-related quality of life (OHRQoL). The Brazilian Economic Classification Criteria (CCEB) was developed by the Brazilian Association of Research Companies [23] for population classification into groups according to economic class.…”
Section: Introductionmentioning
confidence: 99%